Umetne vodne akumulacije za zasneževanje na vzhodu Pohorja (Slovenija) - Klenovšek, Tina (Acta biologica slovenica, 2025)
Artificial water habitats can be breeding sites for amphibians but may also function as ecological traps. Water accumulations for artificial snowmaking are not optimal habitats for amphibians, and little is known about their reproduction in these water bodies. In this study, we sampled amphibians in two accumulations for snowmaking in the Mariborsko Pohorje area. One is located at the foothills of Pohorje (312 m a.) in an urban environment, and the other on the slopes of Pohorje (560 m a.), surrounded by forest that is part of the Natura 2000 Pohorje. In total, we confirmed the reproduction of seven amphibian species in these accumulations: Italian Crested Newt (Triturus carnifex), Alpine Newt (Ichthyosaura alpestris), Smooth Newt (Lissotriton vulgaris), Yellow-bellied Toad (Bombina variegata), Common Toad (Bufo bufo), Common Frog (Rana temporaria), and Agile Frog (Rana dalmatina). The Yellow-bellied Toad and the Italian Crested Newt are qualifying species for the Natura 2000 Pohorje site. In the accumulation at the foothill of Pohorje, where fish were present, amphibian reproduction was unsuccessful. In the accumulation on the slope of Pohorje, where there were no fish, the steep banks (30-60°) with uncovered geomembrane and the low water level led to the mortality of adult Yellow-bellied Toads and numerous (>500) juvenile Rana sp. frogs. The drop in water level also resulted in the stranding of eggs and embryos of the Italian Crested Newt. Snowmaking reservoirs are unsuitable for amphibians in several respects, yet they still use them for breeding. To reduce amphibian mortality, the following measures should be implemented: maintaining maximum water levels during the breeding season (March-July), covering the geomembrane and reducing the bank steepness to facilitate amphibian exit, removing fish through autumn reservoir drainage, and preventing roadkill on roads adjacent to the reservoirs.
Keywords: amphibians; artificial habitat; Bombina variegata; dvoživke; ecological trap; ekološka past; Natura 2000; snowmaking ponds; Triturus carnifex; umetni habitat; vodna zajetja; water reservoirs; zadrževalniki za umetno zasneževanje